(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Even if there are global economic challenges, the Indian economy is one of the fastest-growing. A great deal of change has occurred in the Indian financial system since the stratagem. Customers’ expectations have shifted significantly as a result of competitive and deregulatory forces. Human resource management that is both efficient and effective is crucial for success in this competitive market. Expertise in administration, competitive advantage, and HR policy all had their hypotheses tested. In order to be competitive in the industrial sector, Indian bank managers have good administrative skills. Additionally, they are very competent administrators who can manage human resources policy in both public and private banks. Finding out what problems exist with human resource management in the banking business and how to fix them are the goals of this research. The authors hope their findings will be useful for public and private sector banks alike.